An Employer’s Liability in the Context of Sexual Harassment - Darby, Faye Ann (University of the Witwatersrand, Johannesburg, 2025)
The legal measures taken to prevent and eliminate sexual harassment in the workplace, are all to ensure that there is employment equity and that the rights enshrined in the Constitution of the Republic of South Africa, 1996 (‘the Constitution’), are upheld. This paper aims to determine the scope of employers' vicarious liability for acts of sexual harassment. To achieve this goal, the paper will be divided into two separate sections, the first will canvas the historical development of vicarious liability of employers in connection with cases of sexual harassment together with the applicable common law principles. This will be followed by an analysis of the employer's statutory vicarious liability particularly the changes that occurred between the Code of Good Practice on the Handling of Sexual Harassment Cases in Workplaces GEN N 1357 Gazette 27865 dated August 4, 2005 (‘the Old Code’) and 2022 the Code of Good Practice on the Prevention and Elimination of Harassment in the Workplace GN. R1890 Gazette 46056 dated March 18, 2022 (‘the New Code’). In this analysis, cases and hypotheticals will be used to illustrate the aspirations of the changes in the Codes together with the practical implications. The key findings of the research are that in reality the aspiration of the New Code will most likely not be achieved from a substantive aspect, as the scope of vicarious liability has not been extended beyond that which it was under the Old Code, because the fundamental principles of vicarious liability which are the cornerstones of the Employment Equity Act in section 60, make it practically impossible to hold an employer liable for acts of persons other than those governed under the Employment Equity Act 55 of 1998 (‘EEA’). Regarding the procedural aspect, there appears to be far more onerous obligations placed upon the employer, which would increase liability for employers. In conclusion, the legislature had great intentions concerning the substantive scope, but it was not well executed and needs to go back to the drawing board and possibly develop ways to convert the New Code into binding legislation together with dealing with the treatment of misconduct and discrimination separately but whilst balancing the rights of both parties. Unfortunately, the New Code has failed to achieve the goals we had all hoped for.
A research report submitted in fulfillment of the requirements for the Master of Laws, in the Faculty of Commerce Law and Management, School of law, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Employer’s Liability; Context of Sexual Harassment; SDG-8: Decent work and economic growth; SDG-5: Gender equality